Maturation of viral proteins in cells infected with temperature-sensitive mutants of vesicular stomatitis virus. - Knipe, D M (1977)
Maturation of viral proteins in cells infected with mutants of vesicular stomatitis virus was studied by surface iodination and cell fractionation. The movement of G, M, and N proteins to the virion bud appeared to be interdependent. Mutations thought to be in G protein prevented its migration to the cell surface, allowed neither M nor N protein to become membrane bound, and blocked formation of viral particles. Mutant G protein appeared not to leave the endoplasmic reticulum at the nonpermissive temperature, but this defect was partially reversible. In cells infected with mutants that caused N protein to be degraded rapidly or prevented its assembly into nucleocapsids, M protein did not bind to membranes and G protein matured to the cell surface, but never entered structures with the density of virions. Mutations causing M protein to be degraded prevented virion formation, and G protein behaved as in cells infected by mutants in N protein. These results are consistent with a model of virion formation involving coalescence of soluble nucleocapsid and soluble M protein with G protein already in the plasma membrane.